Hydrogen sulfide donors alleviate itch secondary to the activation of type-2 protease activated receptors (PAR-2) in mice. (November 2016) - Coavoy-Sánchez, S.A.; Rodrigues, L.; Teixeira, S.A.; Soares, A.G.; Torregrossa, R.; Wood, M.E.; Whiteman, M.; Costa, S.K.P.; Muscará, M.N.
Graphical abstract: Abstract: Hydrogen sulfide (H2 S) has been highlighted as an endogenous signaling molecule and we have previously found that it can inhibit histamine-mediated itching. Pruritus is the most common symptom of cutaneous diseases and anti-histamines are the usual treatment; however, anti-histamine-resistant pruritus is common in some clinical settings. In this way, the involvement of mediators other than histamine in the context of pruritus requires new therapeutic targets. Considering that the activation of proteinase-activated receptor 2 (PAR-2) is involved in pruritus both in rodents and humans, in this study we investigated the effect of H2 S donors on the acute scratching behavior mediated by PAR-2 activation in mice, as well as some of the possible pharmacological mechanisms involved. The intradermal injection of the PAR-2 peptide agonist SLIGRL-NH2 (8–80 nmol) caused a dose-dependent scratching that was unaffected by intraperitoneal pre-treatment with the histamine H1 antagonist pyrilamine (30 mg/kg). Co-injection of SLIGRL-NH2 (40 nmol) with either the slow-release H2 S donor GYY4137 (1 and 3 nmol) or the spontaneous donor NaHS (1 and 0.3 nmol) significantly reduced pruritus. Co-treatment with the KATP channel blocker glibenclamide (200 nmol) or the nitric oxide (NO) donor sodium nitroprusside (10 nmol) abolished the antipruritic effects of NaHS; however, the specific soluble guanylyl cyclase inhibitor ODQ (30 μg) had no significant effects. The transient receptor potential ankyrin type 1 (TRPA1) antagonist HC-030031 (20 μg) significantly reduced SLIGRL-NH2 -induced pruritus; however pruritus induced by the TRPA1 agonist AITC (1000 nmol) was unaffected by NaHS. Based on these data, we conclude that pruritus secondary to PAR-2 activation can be reduced by H2 S, which acts through KATP channel opening and involves NO in a cyclic guanosine monophosphate (cGMP)-independent manner. Furthermore, TRPA1 receptors mediate the pruritus induced by activation of PAR-2, but H2 S does not interfere with this pathway. These results provide additional support for the development of new therapeutical alternatives, mainly intended for treatment of pruritus in patients unresponsive to anti-histamines.